Ending the crisis : Mayo Clinic's guide to opioid addiction and safe opioid use - Geyer, Holly L. (Mayo Clinic Press, 2023)
"In Ending the Crisis, addiction medicine specialist Dr. Holly Geyer goes beyond the science of addiction to offer those struggling with opioids a real solution. Developed by trusted Mayo Clinic experts, this empowering and accessible book contains vital information about opioids and addiction, as well as practical tools for recovery, and impactful personal stories from those who've lived through the experience." -- Amazon.com.